Dynamic Pricing Scheme for Resource Allocation in Multi-Cloud Environment - binti Muhamad Shaari, Nurul Ainaa; Ang, Tan Fong; Por, Lip Yee; Liew, Chee Sun (Malaysian Journal of Computer Science, 2017)
Cloud computing has taken the IT and business world by storm through its cost savings and quick-and-easy adoption. Currently, fixed price model is dominating the pricing schemes in the cloud market. However, this model is unable to reflect the current market needs for cost savings as the number of cloud provider and user increases. As a result, a dynamic pricing scheme has emerged as an attractive strategy to better cope with the unpredictable cloud demand. This paper proposed a dynamic pricing scheme that provides fairness among the service providers in a multi-cloud environment. The scheme adjusts the price accordingly to encourage the low utilized resources’ usage and discourage over utilized resources’ usage. The evaluation results showed that the proposed scheme is able to reduce the cost of the end user when running compute-intensive and data-intensive jobs in the multi-cloud environment.